Lower Antiplatelet Effect of Aspirin in Essential Thrombocythemia than in Coronary Artery Disease - Pedersen, Oliver Buchhave; Hvas, Anne-Mette; Ommen, Hans Beier; Kristensen, Steen Dalby; Grove, Erik Lerkevang (TH Open, 2021)
Background Patients with essential thrombocythemia (ET) and coronary artery disease (CAD) have increased risk of thromboembolic complications. In addition, a reduced antiplatelet effect of aspirin has been demonstrated in both patient groups. As ET is a platelet disorder, platelets may be more important for the thromboembolic risk in ET than in CAD. We aimed to investigate the antiplatelet effect of aspirin and platelet turnover in ET versus CAD patients.Methods We included 48 ET patients and an age-matched group of 48 CAD patients. The effect of aspirin was evaluated by thromboxane B2 (TXB2) levels and platelet aggregation. Platelet turnover was assessed by immature platelet count (IPC) and immature platelet fraction (IPF).Results ET patients had reduced effect of aspirin compared with CAD patients, demonstrated by significantly higher TXB2 levels (median of differences = 22.3 ng/mL, p < 0.0001) and platelet aggregation (median of differences = 131.0 AU*min, p = 0.0003). Furthermore, ET patients had significantly higher IPC (p < 0.0001) and IPF (p = 0.0004) than CAD patients.Conclusion ET patients have lower 24-hour antiplatelet effect of aspirin than CAD patients. This may be explained by an increased platelet production and turnover counteracting the antiplatelet effect of aspirin. These findings strengthen the rationale for exploring novel antiplatelet regimens in ET patients to reduce the risk of cardiovascular events.
Keywords: aspirin; essential thrombocythemia; platelet aggregation; thromboxane B2; platelet activation; platelet function test; coronary artery disease